2019
DOI: 10.1007/s11418-019-01332-5
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin suppresses neutrophil infiltration into adipose tissue in high-fat diet-induced obese mice

Abstract: Recruitment of immune cells to adipose tissue is altered dramatically in obesity, which results in chronic inflammation of the adipose tissue that leads to metabolic disorders, such as insulin resistance and type 2 diabetes mellitus. The regulation of immune cell infiltration into adipose tissue has prophylactic and therapeutic implications for obesity-related diseases. We previously showed that naringenin, a citrus flavonoid, suppressed macrophage infiltration into adipose tissue by inhibiting monocyte chemoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“… Preserved endothelium-dependent relaxation in the aortae ( Malakul et al, 2018 ). V. C57BL/6J Mice V. 100 mg/kg V. 14 days V. Naringenin V. Inhibited the infiltration of neutrophils in adipose tissues → reduced the expression of several chemokines MCP -1 and MCP-3, in the adipose tissues ( Tsuhako et al, 2020 ). VI.…”
Section: Discussionmentioning
confidence: 99%
“… Preserved endothelium-dependent relaxation in the aortae ( Malakul et al, 2018 ). V. C57BL/6J Mice V. 100 mg/kg V. 14 days V. Naringenin V. Inhibited the infiltration of neutrophils in adipose tissues → reduced the expression of several chemokines MCP -1 and MCP-3, in the adipose tissues ( Tsuhako et al, 2020 ). VI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in our previous studies, we have shown that the citrus flavonoid, naringenin (100 mg/kg/d), dissolved in methylcellulose reduced macrophage and neutrophil infiltration into the adipose tissue of mice. 17,18) Therefore, we chose to use 0.063 and 0.125% (w/v) GH. This is because when the mouse weight is 20 and 40 g, respectively, the GH dose will be about 100 mg/kg/d.…”
Section: Methodsmentioning
confidence: 99%
“…The SVF was prepared from adipose tissue as previously described. 17,19) Briefly, epididymal fat pads were cut into small pieces and rinsed in an N-(2-hydroxyethyl) piperazine-N′-2-ethanesulfonic acid-based Ringer's solution. The fat pieces were then incubated at 37 °C for 30 min in a collagenase type 1 solution.…”
Section: Preparation Of the Stromal Vascular Fraction (Svf) Of Adiposmentioning
confidence: 99%
“…In a short-term HFD mice model, naringenin can suppress neutrophil and macrophage infiltration into adipose tissue [ 215 ]. Concretely it can inhibit the expression of several chemokines like MCP-1 and MCP-3 [ 217 ]. Eriodyctiol (ED) supplementation on its side lowered the adiposity in diet-induced obese mice by regulating gene expression.…”
Section: Flavanonesmentioning
confidence: 99%